2015
DOI: 10.1186/s12937-015-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and metabolic syndrome in individuals with normal weight: a cross-sectional study

Abstract: BackgroundThe results of several papers have confirmed the existence of correlations between an unhealthy diet and the presence of metabolic syndrome. However, relationships between eating habits and metabolic obesity with normal weight have not yet been sufficiently studied. The aim of the study is to determine which dietary patterns are present in individuals with a normal BMI and to find out whether those patterns were connected with the risk of metabolic syndrome and its features.MethodsA cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 29 publications
(34 reference statements)
6
64
2
1
Order By: Relevance
“…However, these reports have been limited to MHO phenotype [13], especially without considering dietary pattern [14], or with specific age groups [15]. A few studies have reported associations in MONW phenotype in non-US population [16], but with limited generalizability [17]. Several studies demonstrated that dietary factors are related to metabolic phenotype in both obese and normal weight population [18], but only focused on women [19], or single foods such as olive oil [20].…”
Section: Introductionmentioning
confidence: 93%
“…However, these reports have been limited to MHO phenotype [13], especially without considering dietary pattern [14], or with specific age groups [15]. A few studies have reported associations in MONW phenotype in non-US population [16], but with limited generalizability [17]. Several studies demonstrated that dietary factors are related to metabolic phenotype in both obese and normal weight population [18], but only focused on women [19], or single foods such as olive oil [20].…”
Section: Introductionmentioning
confidence: 93%
“…The studies included a questionnaire interview, anthropometric measurements, blood pressure measurements, and analyses of collected fasting-blood samples, on the basis of which the concentration of cholesterol and triglycerides was determined. Detailed information regarding the project, research procedures, and group selection were described in previously published papers [19][20][21]. In brief: 13,172 individuals were examined (4447 men), aged between 37 and 66 years, permanently residing in the Kielecki Region in Poland.…”
Section: Methodsmentioning
confidence: 99%
“…The studies included blood pressure measurements and analyses of collected fasting-blood samples, on the basis of which the concentration of cholesterol, glucose, and triglycerides was determined, anthropometric measurements (waist circumference) were taken, and a questionnaire interview conducted. Detailed information regarding the project, research procedures and group selection were described in previously published papers [28][29][30]. In brief: 13,172 individuals were examined (4447 men), aged between 37 and 66 years, permanently residing in the Kielecki region in Poland.…”
Section: Methodsmentioning
confidence: 99%